KUALITAS LAYANAN HOTEL BERBINTANG TIGA, EMPAT, DAN LIMA DI SURABAYA - Erna Andajani (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2005)
The Leisure and tourism industry in East java has shown good improvement and brought impact to hotel industry, As we know hotel is one of the businesses that depend mostly on service quality that perceived by the customers. In otherway, hotel also has aspect of physical and non physical facility, and categorized by government in order like five star hotel, four star hotel, and so on. Some of customer has shown that they do not really care about this rank, but on what, service quality they perceived.